Referentiality and transgression: representations of incest and child sexual abuse in American literature of the twentieth century - Nesteruk, Peter (1994)
This thesis will consider the incest theme in twentieth century American literature. Antecedents will be considered, especially the rich traditions of the late eighteenth and nineteenth centuries, but the main focus will be on three writers central to the American canon: F. Scott Fitzgerald, William Faulkner, and Vladimir Nabokov. All three of these writers have produced texts in which their claim to literary fame and their appropriation of the incest theme are inextricable: namely, Fitzgerald's Tender is the Faulkner's The Sound and the Fury, Absalom, Absalom! and Go Down, Moses, and Nabokov's Lolita. I will conclude with a chapter which examines how this debt to literary tradition, this canonical pride of place of the incest theme, has been transformed in its trajectory through the latter half of the twentieth century.